РОЗРОБКА СТРУКТУРИ СЛОВНИКА ДЛЯ ЧАТ-БОТУ КАТАЛОГУ ОСВІТНІХ ПОСЛУГ ЗАКЛАДУ ВИЩОЇ ОСВІТИ - SHILINH, Anna; PASKO, Anastasiia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The aim of this article is to develop a dictionary structure for a chatbot of educational services catalog of the higher education institution. The quality of information support for consumers of educational services depends on the timeliness and reliability of the information provided. If the World Wide Web user does not receive information from official sources of the higher education institution (HEI), this may cause a negative impact on the information system of the higher education institution. The motivational intentions of the official web resources users of the higher education institution in thematic requests to the chatbot correspond to specific sections in the educational services catalog of the higher education institution. Therefore, the lexical selection of motivational intentions, which are characterized by keywords in the thematic query, makes it possible to clearly formulate/correct the completeness of the provision of relevant information. This will make it possible to rationally use the communication process between higher education institution and educational services consumers. As a result of the research, the structure of the lexical content of the dictionary for the chatbot of the educational services catalog is proposed, taking into account the peculiarities of the formation of users information needs from official web resources of the higher education institution. Each thematic request to the proposed chatbot is characterized by a set of keywords that correspond to certain sections of the educational services catalog of the higher education institution. The importance of these keywords are determined by the weighting factor, which shows the relevance of the thematic query to the section of the educational services catalog. For this, a statistical indicator was used, which evaluates the keywords in the query and reduces the importance of common words. The results of the research are applied and can be used for effective communication between the higher education institution and consumers of educational services using HEI’s official resources for effective planning of educational services.